Heart Failure Relapses in Response to Acute Stresses – Role of Immunological and Inflammatory Pathways - Hasselbach, Lisa; Weidner, Johannes; Elsässer, Albrecht; Theilmeier, Gregor (Frontiers in Cardiovascular Medicine, 2022)
Cardiovascular diseases continue to be the most imminent health care problems in the western world, accounting for numerous deaths per year. Heart failure (HF), namely the reduction of left ventricular function, is one of the major cardiovascular disease entities. It is chronically progressing with relapsing acute decompensations and an overall grave prognosis that is little different if not worse than most malignant diseases. Interestingly acute metabolically and/or immunologically challenging events like infections or major surgical procedures will cause relapses in the course of preexisting chronic heart failure, decrease the patients wellbeing and worsen myocardial function. HF itself and or its progression has been demonstrated to be driven at least in part by inflammatory pathways that are similarly turned on by infectious or non-infectious stress responses. These thus add to HF progression or relapse. TNF-α plasma levels are associated with disease severity and progression in HF. In addition, several cytokines (e.g., IL-1β, IL-6) are involved in deteriorating left ventricular function. Those observations are based on clinical studies using inhibitors of cytokines or their receptors or they stem from animal studies examining the effect of cytokine mediated inflammation on myocardial remodeling in models of heart failure. This short review summarizes the known underlying immunological processes that are shared by and drive all: chronic heart failure, select infectious diseases, and inflammatory stress responses. In conclusion the text provides a brief summary of the current development in immunomodulatory therapies for HF and their overlap with treatments of other disease entities.